EVOLUSI MONETER SYARIAH: MENELUSURI SEJARAH DAN TRANFORMASI EKONOMI MONETER ISLAM - Nor Amini Annisa; Helma Nadirah; Erwan Setyanor (PT. Saha Kreasi Indonesia, 2026)
Islamic monetary economics represents a long-standing tradition of policy and practice originating from the prophetic era, emphasizing social justice and maintaining money’s role as a medium of exchange and unit of account. This paper examines the evolution of Islamic monetary instruments—from the standardized use of dinars and dirhams, through the nationalization and minting of coins during the Umayyad period, to the emergence of non-cash instruments and negotiable instruments in the Abbasid era. It also reviews classical thinkers such as Ibn Taymiyyah, al Maqrizi, and Ibn Khaldun, who contributed insights on monetary distortions, inflationary causes, and the linkage between currency value and economic productivity. In the post Bretton Woods modern context, most scholars accept fiat money as a legitimate medium of payment based on thamaniah and social custom (‘urf), while insisting on Sharia compliant policy tools. Proposed alternatives include Islamic reserve requirements, profit sharing mechanisms, moral suasion, and sukuk issuance to manage market liquidity equitably. The paper concludes that Islamic monetary evolution aims to sustain the circulation of value in support of the real sector and to promote economic inclusivity.